Gender differences and dynamics of stress response among employees of special services - N.E. Lysenko; A.N. Kharicheva (Психология и право)
Context and relevance. The relevance of the study of operational stress in men and women is determined by the lack of research on gender differences in response to operational stress in the context of the growing trend towards gender equality in extreme professional activities. Methods and materials. In an experimental study with two test stages, including stressful audio and video stimuli, the vegetative and central stress response mechanisms were studied in groups of law enforcement officers — 203 men and 125 women. Results. The results showed that in the group of men, when presented with stressors, more pronounced changes in physiological parameters, a high level of activation, a state of increased functional tension of adaptation mechanisms, high involvement of memory mechanisms in processing stimuli were revealed; repeated exposure to stress stimuli leaded to a deficit of functional adaptation resources. In women an optimal functional state during both primary and repeated stressful exposure despite the high level of attention to stressful stimuli was noted, and a high level of recovery processes after both the first and second exposure to stress stimuli was revealed. Conclusion. The results of the study describing gender differences in the dynamics of the functional state under operational stress, including the processes of physiological resource reduction and recovery, are presented.